2005
DOI: 10.1007/s10533-005-4107-5
|View full text |Cite
|
Sign up to set email alerts
|

Water chemistry and nutrient budgets in an undisturbed evergreen rainforest of Southern Chile

Abstract: In a pristine evergreen rainforest of Nothofagus betuloides, located at the Cordillera de los Andes in southern Chile (41 8S), concentrations and fluxes of nutrients in bulk precipitation, cloud water, throughfall water, stemflow water, soil infiltration and percolation water and runoff water were measured. The main objectives of this study were to investigate canopy-soil-atmosphere interactions and to calculate input-output budgets. From May 1999 till April 2000, the experimental watershed received 8121 mm wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 30 publications
1
45
0
7
Order By: Relevance
“…On both interannual and interdecadal time scales, a coupling is thus apparent between upwelling-favorable conditions over the California Current and the frequency of coastal fog in northern California. The atmospheric conditions that enhance nutrient supply in the surface ocean via upwelling may provide similar benefits to coastal forests via wet deposition of nitrogen in fog water, as observed in California coast redwoods (7) and in Chile (32,33).…”
Section: Resultsmentioning
confidence: 96%
“…On both interannual and interdecadal time scales, a coupling is thus apparent between upwelling-favorable conditions over the California Current and the frequency of coastal fog in northern California. The atmospheric conditions that enhance nutrient supply in the surface ocean via upwelling may provide similar benefits to coastal forests via wet deposition of nitrogen in fog water, as observed in California coast redwoods (7) and in Chile (32,33).…”
Section: Resultsmentioning
confidence: 96%
“…Además, se medirán los aportes de agua por precipitaciones dentro y fuera del bosque y la cantidad proveniente por intercepción de la neblina por un período superior a un año. Este aporte adicional de agua también fue mencionado por otros autores para los bosques templados del sur de Chile (Veblen y Ashton 1982, Pérez et al 1991, Weathers et al 2000, Oyarzún et al 2004.…”
Section: Introductionunclassified
“…Aerosol and gases can by deposited directly from the air to plant and soil surfaces during rainless periods by dry deposition. Wet deposition is defined as the input of atmospheric compounds to the earth´s surface by rain, hail, snow and/or occult deposition that occurs via fogs and clouds, which can be important in mountainous regions [3]. During rain events, dry deposition is washed off from plant parts and, together with wet deposition, reaches the forest floor as throughfall and stem flow.…”
Section: Introductionmentioning
confidence: 99%
“…The annual mean temperature is 5 to 12° C and precipitation ranges from 2000 to 7000 mm in the AMR [3]. Data from [5] reported that mean annual N composition of the rainwater in the CMR and AMR ranges (41°-43° S), varied between < 30 -43 NO 3 --N µg L -1 and 9. [7,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation